Prevalence of pesticide related occupational diseases among Indonesian vegetable farmers – A collaborative work - Sri Awalia Febriana; Miya Khalidah; Fariz Nurul Huda; Sri Sutarni; Indra Mahayana; Niken Indrastuti; Ismail Setyopranoto; Fajar Waskito; Suhardjo Prawiroranu; Ery Kus Dwianingsih; Rusdy Ghazali Malueka (Toxicology Reports, 2023)
Objective: This study was done to understand the prevalence of various occupational diseases including dry eyes, nail dystrophy, and neuropathy related to pesticide exposure in Indonesian local vegetable farmers. Methods: The data were collected through questionnaires and physical examination involving dermatology, neurology, and ophthalmology domains at Ngablak District, Magelang, Central Java directed to local vegetable farmers. Ocular Surface Disease Index (OSDI) questionnaire and the Schirmer test were used. Analysis was done using descriptive statistics using the Statistical Package for the Social Sciences (SPSS 21.0) and presented in tables. Results: Inadequate spraying equipment and improper storage of pesticides were found. Out of 105 farmers, 41.9 % experienced occupational skin diseases (OSD). Definite cognitive impairments were found in 3.4 % of subjects but probable in 28.3 % of subjects. Neuropathies were found in 61.7 % of subjects, and dry-eyes syndrome were found in 28.78 % of subjects. Conclusion: There was a high prevalence of peripheral neuropathy and tremor, dry eyes syndrome in one-third of the population, and the most common skin problem was nail discoloration, with a low incidence of contact dermatitis.